Plant sterols and cardiovascular disease: a systematic review and meta-analysis - Genser, Bernd; März, Winfried (European heart journal, 2012)
Abstract. The impact of increased serum concentrations of plant sterols on cardiovascular risk is unclear. We conducted a systematic review and meta-analysis a
Gesehen am 04.05.2018